Curating Sovereignty in Palestine: Voluntary Grassroots Organizations and Civil Society in the West Bank and East Jerusalem - Herrold, Catherine E (Middle East law and governance, 2022)
Abstract This article extends the literature on "ngo-ization" in the Middle East and Global South to examine "voluntary grassroots organizations" (vgo s): groups that operate on a voluntary basis and position themselves outside of the formal ngo sector and foreign aid system. Based on nine months of ethnographic research in the West Bank and East Jerusalem, the article examines how vgo s use heritage practices as a two-pronged challenge to the ngo-ization of Palestinian civil society. Whereas ngo-ization depoliticized civil society, vgo s resist depoliticization by mobilizing Palestinians to counter the Israeli occupation. And whereas ngo-ization professionalized civil society, vgo s resist professionalization by building large volunteer bases, emphasizing long-term processes of citizen mobilization rather than short-term outcomes, and remaining grounded in local communities and accountable to local citizens. Their work reflects larger trends around the world in which civic actors turn to informal organizing in an era of growing disenchantment with traditional ngo s.